IDENTIFICATION OF TAX MANAGEMENT IN EARNINGS MANAGEMENT IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2016-2019 - Azelita, Novia; Prihandini, Wiwiek (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this research to identify tax management which is explained through tax planning, deferred tax expense and tax avoidance. In this research the sample used was manufacturing companies listed on the Indonesia Stock Exchange during the 2016 until 2019 period, 38 company sample with four years of research produced 152 data were obtained by purposive sampling. The data used was panel data and analysis technique using multiple regressions analysis with Eviews software. The result showed that the tax planning and tax avoidance have a significant effect on earning management, but the coefficient of determination is low at 3,28%. Meanwhile, deferred tax expense have no significant effect on earnings management on manufacturing companies. However, research shows that the higher the profit earned by the company, the lower the tax payable ratio. The tax government should be supervise low income group companies because they have a tendency to reduce taxes. Keywords: Tax Planning, Deferred Tax Expense, Tax Avoidance, Effective Tax Rate.